Trust Profiles: Associations With Psychological Need Satisfaction, Work Engagement, and Intention to Leave - Heyns, Marita; Rothmann, Sebastiaan (Frontiers in Psychology, 2021)
The study aimed to identify trust profiles in the work domain and to study how these patterns related to psychological need satisfaction, work engagement, and intentions to leave. A cross-sectional survey with a convenience sample (N = 298) was used. The Behavioral Trust Inventory, the Work-related Basic Need Satisfaction Scale, the Work Engagement Scale, and the Turnover Intention Scale were administered. The results showed four trust profiles: skeptic, reliance-based, moderately cautious, and optimistic trustors represented participants' responses on behavioral trust. Skeptic and optimistic trustors (who represented about 50% of the sample) differed primarily regarding their reliance and disclosure intensity. The other two trust profiles (representing the other 50% of the sample) reflected higher reliance and lower disclosure or lower reliance and higher disclosure. Psychological need satisfaction (comprised of autonomy, competence, and relatedness satisfaction) and work engagement were the strongest and intentions to leave the weakest for optimistic trustors (compared to skeptic trustors).